1993
DOI: 10.1016/s0006-3495(93)81473-5
|View full text |Cite
|
Sign up to set email alerts
|

Orientational behavior of phosphatidylcholine bilayers in the presence of aromatic amphiphiles and a magnetic field

Abstract: A number of aromatic-containing additives which can influence the orientation of fragments of lipid bilayer membranes by a magnetic field have been investigated. Two properties of these additives prove important: (1) sufficient detergency to facilitate reorganization of bilayer components and (2), sufficient anisotropy in magnetic susceptibility the preferred direction of fragment orientation. Triton X-100 is identified as effective in terms of facilitating magnetic field ordering of bilayer fragments but does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 23 publications
2
37
0
Order By: Relevance
“…This was first observed when an aromatic amphiphile, 1-naphtol, was added to DMPC/CHAPSO bicelles (53). High concentration of the ion channel gramicidin A was also found to flip the bicelle alignment (62,63).…”
Section: Parallel-oriented Bicellesmentioning
confidence: 89%
See 1 more Smart Citation
“…This was first observed when an aromatic amphiphile, 1-naphtol, was added to DMPC/CHAPSO bicelles (53). High concentration of the ion channel gramicidin A was also found to flip the bicelle alignment (62,63).…”
Section: Parallel-oriented Bicellesmentioning
confidence: 89%
“…This method allows the assignment of the 13 C resonances by following peaks to their isotropic position, and the calculation of the CSA (11,53).…”
Section: Determination Of the Structure And Orientation Of Membrane-bmentioning
confidence: 99%
“…H'-transporting ATP synthase (EC 3.6.1.34). new approach to produce magnetically orientable phospholipid bilayers useful for NMR experiments (Sanders et al, 1993;Sanders and Prestegard, 1990). Both Chaps and Chapso have been used in reconstitution studies and some reports appeared in the literature dealing with the formation of active proteoliposomes (Yoda et al, 1984;Helmke and Howard, 1987).…”
Section: -~-mentioning
confidence: 99%
“…It is consequently desirable to use a bilayered model system that spontaneously aligns with the bilayer normal parallel to the applied magnetic field. Parallel alignment of phospholipid bilayers has been shown to be feasible by altering the magnetic susceptibility anisotropy of the membrane through the addition of either large amounts of aromatic molecules (9) or small amounts of the trivalent lanthanide ions Eu 3ϩ , Er 3ϩ , Tm 3ϩ , and Yb 3ϩ (10,11). In particular, it has been recently shown that less than 1 mol% Tm 3ϩ or Yb 3ϩ , relative to DMPC, is needed to induce parallel alignment (12).…”
Section: Introductionmentioning
confidence: 99%